Strategi Perguruan Tinggi Keagamaan Islam Negeri Dalam Mencetak Generasi Akuntan Syariah Di Era Digital - Ummu Najwa; Rohayatul Akyani; Armaelis Arfani; Elsa Tiara; Gunawan Aji (CV. Aksara Global Akademia, 2023)
Increasingly sophisticated technological developments have an impact on the world of work, such as the world of Sharia accounting. This study aims to analyze the opportunities and challenges of Islamic accountants in the digital era and the strategies carried out by state Islamic religious universities so that they can produce a generation of Islamic accountants who are able to keep up with this digitalization flow. The research method used is a qualitative approach and data sources were obtained through a literature review. The results of this study state that the influence of digital technology in the world of Sharia accounting will create opportunities and challenges that Sharia accountants must be prepared to face. Starting from the opportunity for a new work system for the Islamic accounting profession itself to the challenges that later Islamic accountants must be ready to compete with sophisticated technology. It is a big record for every agency that gave birth to a generation of Sharia accountants in the current era of digitalization. They are required to be able to produce a generation of accountants with quality, integrity, and capacity in their field. Therefore, several strategies that can be used include preparing quality human resources by preparing a platform for human resource development, increasing leadership and teamwork skills, and the need for new literacy to prepare more competitive Sharia accounting graduates.